PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TUTOR SEBAYA GUNA MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS V SDN 089 PANYABUNGAN - Zahara, Rita (JGK (Jurnal Guru Kita), 2018)
Abstract: The Application of Co-operative Learning of Tutor Type Sebaya To Increase Student Achievement of Mathematics Student of Class V SDN 089 Panyabungan. This study aims to improve students’ mathematics learning achievement. The subjects of this study are the students of grade V SDN 089 Panyabungan with the number of students 31 people. Beginning of KBM test result of learning (Pretes), result of student learning average 34.84 it shows that student rarely read book before studying in school. Then continued KBM, the end of KBM to II and KBM to IV test result of formative study I and formative II. The average learning outcomes in each formative show 59.35 and 81.29. Student activity data according to observation in cycle II are read / write (23%), doing LKS (42%), asking fellow friend (12%), answer friend’s question (14%) ask teacher (5%), not relevant to KBM (4%). Keywords: Peer Tutor Learning Model, learning outcomes, learning activities Abstrak: Penerapan Pembelajaran Kooperatif Tipe Tutor Sebaya Guna Meningkatkan Prestasi Belajar Matematika Siswa Kelas V SDN 089 Panyabungan.Penelitian ini bertujuan untuk meningkatkan prestasi belajar matematika siswa.Subjek penelitian ini adalah siswa kelas V SDN 089 Panyabungandengan jumlah siswa 31 orang. Awal KBM dilakukan tes hasil belajar (Pretes), hasil belajarsiswa rata-rata 34.84hal tersebut menunjukkan bahwa siswa jarang membaca buku sebelum pembelajaran disekolah. Kemudian dilanjutkan KBM, akhir KBM ke II dan KBM ke IV dilakukan tes hasil belajar formatif I dan formatif II. Rata-rata hasil belajarpada formatif masing-masing menunjukkan 59.35 dan 81.29. Data aktivitas siswa menurut pengamatan pada siklus II antara lain membaca/menulis (23%), mengerjakan LKS (42%), bertanya sesama teman (12%), menjawab pertanyaan teman (14%) bertanya kepada guru (5%), dan yang tidak relevan dengan KBM (4%). Kata kunci : Model Pembelajaran Tutor Sebaya, hasil belajar, aktivitas belajar